Pedagogic guide for teaching english language and english for specific purposes applied to police procedures in the curriculum of the policemen´s training course in the horsemanship and Remount School at Tambillo Town 2008 - Taco Villalta, Gonzalo (2008)
The field of language teaching has undergone deep changes during the last 30 to 40 years, following this perception; I decided to do this research, following the direction and support of my tutors and based on my academic preparation in the Army Polytechnic School. First of all, I selected the subject to be investigated, because I work as policeman in the Horsemanship and Remount School where I have had experience, so I would like to apply my English knowledge in this research. I found that during the training course for policemen the English subject is not included in the curriculum, and with the suggestions of some policemen and even some applicants, I found the necessity to include this important subject in the curriculum of policemen´s training course. The main problem is that the Horsemanship and Remount School in the curriculum of the policemen´s training course doesn t include the English language as subject, and in the daily activities the new police officers really needs to know English to make an efficient work for the society, but especially with the migration police services, tourism police services where they really need a good English level. Once identified the main problem I started to work in the theorical framework in which I will support my research. Finally I collected the necessary information to carry out this project, and I am sure that this research will help the new applicants of the Horsemanship and Remount School to get a good English level.